Effect of a hybrid teaching games for understanding/sport education unit on elementary students' self-determined motivation in physical education. (May 2021) - Gil-Arias, Alexander; Harvey, Stephen; García-Herreros, Francisco; González-Víllora, Sixto; Práxedes, Alba; Moreno, Alberto
As an alternative to the direct instructional model, Metzler proposed a range of pedagogical models that include second generation models such as teaching games for understanding (TGfU) and sport education (SE). These pedagogical models have key design features that can promote high levels of autonomous motivation for both boys and girls. Consequently, the purpose of this study was to investigate the motivational outcomes of elementary boys and girls as they participated in an invasion game unit through two pedagogical models: a hybrid TGfU/SE unit or a direct instruction unit. Participants were 292 elementary school students (mean age = 10.41, standard deviation age = 0.49), who were taught through a hybrid TGfU/SE unit or a more traditional teacher-centred format within a pre-intervention/post-intervention quasi-experimental design. The hybrid unit was designed according to the characteristics of SE, while learning tasks were designed to integrate the pedagogical principles of TGfU. A 2 (pedagogical model) × 2 (test-time) × 2 (gender) multivariate analysis of variance was performed to detect between-groups and within-group differences. Significant differences in student motivation were observed for both boys and girls who participated in the hybrid TGfU/SE unit in both analyses across all motivational outcomes. Despite the existence of social stereotypes in terms of physical activity, teachers' use of hybrid TGfU/SE units promotes an autonomy-supportive, inclusive, and equitable learning environment where all students, regardless of their gender and/or content focus of the unit and have opportunities to increase their engagement, enjoyment, and social interactions within physical education lessons.